The Multivariate Effect of Ketamine on PTSD: Systematic Review and Meta-Analysis - Du, Rui; Han, Ruili; Niu, Kun; Xu, Jiaqiao; Zhao, Zihou; Lu, Guofang; Shang, Yulong (Frontiers in Psychiatry, 2022)
Background: Post-traumatic stress disorder (PTSD) is a serious stress-related disorder caused by traumatic experiences. However, identifying a key therapy that can be used for PTSD treatment remains difficult. Ketamine, a well-known dissociative anesthetic, is considered safe to be used in anesthesia, pain management, and antidepressant actions since 1970. At present, it is still controversial whether PTSD can be treated with ketamine. The authors performed a meta-analysis to determine whether the use of perioperative ketamine lowers the incidence of PTSD. Method: Cochrane Central Register of Controlled Trials, Embase, PubMed, and Web of Science were searched to examine the use of ketamine for the treatment of PTSD among soldiers with combating experience. Studies were included if they were randomized placebo-controlled, case-control, and cohort studies. The primary outcome was the incidence of PTSD in the later stage of the wounded or burn soldiers. The secondary outcome was the influence of ketamine on PTSD-scale scores for early and chronic PTSD, respectively. Results: Our search yielded a total of three studies (n=503 patients) comparing the use of ketamine (n=349) to control (n=154). The available evidence showed no significant difference in the incidence of PTSD between combatant soldiers on the battlefield with or without ketamine treatment (risk ratio = 0.81, 95% CI, 0.63—1.04; P=0.10). In 65 patients from three trials, ketamine was not only ineffective in treating early PTSD but also lead to exacerbation of the disease (risk ratio = 2.45, 95% CI, 1.33—3.58; P<0.001). However, in 91 patients from the other three trials, ketamine is effective in treating chronic PTSD (risk ratio = -3.66, 95% CI, -7.05—-0.27; P=0.03). Conclusion: Ketamine was not effective on lower the PTSD incidence for soldiers on the battlefield, nor on the PTSD-scale scores in early PTSD patients. However, it may improve the PTSD-scale scores for chronic conditions.